Tailing sand aggregate, ultra-high performance concrete and application thereof
By optimizing the particle size and gradation of tailings sand aggregate, and combining it with cementitious materials and admixtures, ultra-high performance concrete was prepared, solving the problem of insufficient strength caused by tailings aggregate replacing quartz sand, and achieving high strength and resource conservation in concrete.
Patent Information
- Application Number
- CN202411344409.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
In existing technologies, when tailings aggregate is used to replace quartz sand as aggregate for ultra-high performance concrete, the compressive and flexural strength of the concrete is insufficient, and it is difficult to achieve efficient utilization of all solid waste tailings.
By optimizing the particle size and gradation of tailings sand aggregate to below 380 micrometers, and combining it with a specific proportion of cementitious materials, admixtures and fibers, ultra-high performance concrete is prepared, achieving dense packing of aggregates and improving the flexural and compressive strength of concrete.
It achieves high flexural and compressive strength in ultra-high performance concrete, solving the problem of insufficient strength caused by tailings aggregate replacing quartz sand in existing technologies, while realizing efficient utilization and resource conservation of all solid waste tailings.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to tailings sand aggregate, ultra-high performance concrete and applications thereof. Background Art
[0002] Ultra-High Performance Concrete (UHPC), characterized by ultra-high strength, toughness and durability, has become a new system that achieves a major leap in the performance of cement-based materials. Compared with ordinary concrete, ultra-high performance concrete can greatly reduce the amount of materials used, reduce construction costs, save resources, and reduce production, transportation and construction energy consumption. The use of ultra-high performance concrete will contribute to environmental protection.
[0003] The most important way to utilize tailings as building materials is to use them as raw materials for building materials such as concrete and mortar. However, the disposal method of building materials still has problems such as low solid waste content, low product performance, low added value, and prominent cost-performance contradiction. In recent years, in order to efficiently recover valuable metals, the concentrator has used ultrafine grinding technology to improve the dissociation degree of mineral monomers, resulting in the current output of tailings becoming finer and finer, making it difficult to directly use them as aggregates for ordinary concrete.
[0004] These fine iron tailings can partially replace quartz sand as an aggregate for making ultra-high performance concrete. Zhao et al. and Zhu et al. studied the effect of replacing sand with tailings on the performance of UHPC. With a 20% replacement, the 28-day strength of UHPC was still comparable to that of UHPC without iron ore tailings. Pyo et al. used a quartz-based tailings to partially replace quartz sand (30% by mass) in UHPC and obtained a strength comparable to that of UHPC with quartz sand. However, completely replacing sand with tailings reduces the strength of UHPC, and 100% replacement of natural aggregates with tailings significantly reduces the material's workability and compressive strength.
[0005] The Chinese patent application with publication number CN110698098A discloses a corrosion-resistant iron tailings (waste rock) aggregate, comprising the following components: six graded tailings with particle sizes of 25-27mm, 18-20mm, 15-17mm, 8-10mm, 4-5mm and 2-3mm; the mass percentages of the graded tailings are 4-6%, 18-22%, 24-26%, 24-26%, 18-22% and 4-6%, respectively, which can significantly reduce the void ratio of the aggregate, make the iron tailings aggregate more compact, and achieve the effect of enhancing the corrosion resistance of the iron tailings aggregate. Further, a corrosion-resistant concrete comprising the corrosion-resistant iron tailings aggregate is disclosed, but there is a technical problem in the prior art that the compressive strength of the concrete needs to be improved. Summary of the invention
[0006] The first invention objective of the present invention is to further improve the compressive strength of concrete using tailings aggregate. On this basis, the first aspect of the present invention provides a tailings sand aggregate, comprising tailings sands of 40-90 mesh, 90-400 mesh, and 400-1250 mesh in a mass ratio of 1:0.6~3:0.4~2. Preferably, the tailings sand aggregate comprises tailings sands of 40-90 mesh, 90-400 mesh, and 400-1250 mesh in a mass ratio of (20-50): (30-60): (20-40).
[0007] Generally, when tailings sand aggregate is used to replace quartz sand, the tailings sand aggregate used is basically millimeter-level with the same grade as the original quartz sand particles, but because the strength of tailings sand is weaker than that of quartz sand, it is easy to crack itself or with the interface transition zone when subjected to force. Therefore, directly using tailings aggregate to replace quartz sand as aggregate will reduce the strength of concrete. The present invention calculates through Griffith microcrack theory and finds that controlling the particle size of the tailings sand aggregate to be below 380 microns can significantly reduce the possibility of crack expansion, thereby improving the strength of concrete; based on this, the present invention further optimizes the particle size range and gradation of tailings sand, so that the tailings sand aggregate provided by the present invention is used to prepare concrete, which can achieve close stacking of concrete, thereby making the concrete have higher flexural and compressive strengths, and the concrete involved includes but is not limited to ultra-high performance concrete.
[0008] Preferably, the tailings sand aggregate comprises tailings sands of 40-90 mesh, 90-400 mesh, and 400-1250 mesh in a mass ratio of 1:1-1.5:0.5-1. More preferably, the tailings sand aggregate comprises tailings sands of 40-90 mesh, 90-400 mesh, and 400-1250 mesh in a mass ratio of (30-40): (40-50): (20-30).
[0009] The invention further optimizes the gradation of the tailings sand aggregate, so that the obtained concrete has better mechanical properties such as flexural strength and compressive strength.
[0010] In some embodiments of the present invention, the tailings sand is selected from at least one of iron tailings, vanadium-titanium magnetite tailings, molybdenum tailings, copper tailings and gold tailings. The present invention uses the siliceous tailings with SiO2 as the main component, and the particle strength is high. The obtained tailings sand aggregate is used to prepare concrete, and the effect of improving the flexural strength and compressive strength of concrete is the best.
[0011] The tailings sand aggregate provided by the invention is used for preparing concrete and can improve the compressive strength and flexural strength of the concrete through the most dense stacking of materials.
[0012] The second aspect of the present invention provides an ultra-high performance concrete, comprising 30-85wt% of the above-mentioned tailings sand aggregate. Preferably, 35-70wt% of the above-mentioned tailings sand aggregate is contained. The ultra-high performance concrete provided by the present invention adopts a high dosage of the above-mentioned tailings sand aggregate, and realizes the full solid waste tailings replacing the quartz sand in the concrete; at the same time, tailings resources can be utilized in large quantities, which not only reduces costs, but also rationally utilizes resources and reduces environmental pollution; at the same time, the tailings sand aggregate provided by the present invention with a particle size controlled at less than 380 microns can make the ultra-high performance concrete densely stacked, thereby overcoming the deficiencies in flexural strength and compressive strength caused by using millimeter-level tailings sand aggregates to replace quartz sand in the prior art, and achieving the mechanical properties of the obtained ultra-high concrete such as improved flexural strength and compressive strength, which are equivalent to or even higher than the ultra-high concrete obtained by using quartz sand.
[0013] Preferably, the ultra-high performance concrete further comprises a cementitious material, and the mass ratio of the cementitious material to the tailings aggregate is 1:0.5~2.5, preferably 1:0.5~2.0, and more preferably (8-15):(8-12). In the present invention, the ratio of the cementitious material to the tailings aggregate is within this range calculated by the MAA model, which can ensure the tight stacking of the whole material. At the same time, considering the volume shrinkage of the cementitious material after the hydration reaction, the proportion of the cementitious material is appropriately increased during the batching process.
[0014] In some preferred embodiments of the present invention, the cementitious material comprises cement and an auxiliary cementitious material, and the auxiliary cementitious material is selected from at least one of fly ash, slag powder, silica fume, limestone powder and zeolite powder.
[0015] In some preferred embodiments of the present invention, the particle size of the auxiliary gelling material is 10-150 μm.
[0016] In some preferred embodiments of the present invention, the cement is silicate cement, such as PI 42.5 cement or P.I52.5 cement.
[0017] The present invention adopts the above-mentioned cementitious material and the tailings sand aggregate to be compounded according to a specific ratio, which can further improve the flexural and compressive strengths of the ultra-high performance concrete.
[0018] In some preferred embodiments of the present invention, the ultra high performance concrete further comprises 1.5-2 wt % of admixture.
[0019] In some preferred embodiments of the present invention, the admixture is selected from at least one of an expander, a water reducer, a retarder, and a defoamer.
[0020] In some preferred embodiments of the present invention, the ultra-high performance concrete further comprises 0.2-20wt% fiber; preferably, the aspect ratio of the fiber is 10-200, and more preferably, the fiber is selected from at least one of polypropylene fiber, steel fiber, carbon fiber, polyoxymethylene fiber, and polyvinyl alcohol fiber.
[0021] In some preferred embodiments of the present invention, the ultra-high performance concrete comprises the following components, measured by weight: 400-1500 parts of cement, 600-1800 parts of tailings sand aggregate, 100-200 parts of silica fume, 0-200 parts of fly ash, 0-150 parts of mineral powder, 5-200 parts of fiber, 25-40 parts of water reducer, 0.01-0.2 parts of defoamer, and 150-190 parts of water.
[0022] In some preferred embodiments of the present invention, the ultra-high performance concrete comprises the following components, measured by weight: 450-1000 parts of cement, 600-1600 parts of tailings sand aggregate, 120-180 parts of silica fume, 50-150 parts of fly ash, 50-100 parts of mineral powder, 100-150 parts of fiber, 30-40 parts of water reducer, 0.05-0.15 parts of defoamer, and 160-180 parts of water.
[0023] The method for preparing ultra-high performance concrete provided by the present invention comprises the following steps: (1) Mix the cementitious material and tailings sand aggregate and stir for 30 seconds to obtain a mixture; (2) mixing water, a water reducing agent, a defoaming agent and the mixture, and stirring for 150 seconds to obtain a fresh concrete slurry; (3) Mixing the fiber with the fresh concrete slurry and stirring for 120 seconds to obtain a fresh ultra-high performance concrete slurry.
[0024] The mixing method adopted in the present invention is conducive to more uniform mixing of materials and good concrete fluidity, which lays a foundation for preparing ultra-high performance concrete with excellent performance.
[0025] The ultra-high performance concrete provided by the present invention has good mechanical strength and can be widely used in the fields of building materials, pavement materials, bridge engineering, etc.
[0026] Generally, the interface transition zone of aggregates in ultra-high performance concrete is often the weak link of concrete, and the destruction of ultra-high performance concrete often starts from here. The present invention calculates through Griffith microcrack theory and finds that controlling the aggregate particle size below 380 microns can reduce the possibility of crack expansion, thereby improving the strength of ultra-high performance concrete. On this basis, the present invention optimizes the particle size and gradation of tailings sand, so that the tailings sand aggregate provided by the present invention is used to prepare concrete, which can achieve the close stacking of the ultra-high performance concrete, thereby making the obtained concrete have higher mechanical properties such as flexural strength and compressive strength.
[0027] The ultra-high performance concrete provided by the present invention adopts the above-mentioned cementitious material to improve its mechanical properties such as flexural strength and compressive strength; by optimizing the ratio of the cementitious material to the aggregate, the overall density of the hydration product and the aggregate is ensured, thereby further improving the strength of the ultra-high performance concrete; the water-cement ratio can be reduced by adopting the water-reducing agent; the harmful bubbles of larger size can be eliminated by adopting the defoaming agent, thereby improving the flexural and compressive strengths of the ultra-high performance concrete; the fiber can further improve the flexural and compressive strengths of the ultra-high performance concrete. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described in conjunction with specific embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the following embodiments, low-silica iron tailings refer to iron tailings with a SiO2 content lower than 65%, and high-silica iron tailings refer to iron tailings with a SiO2 content higher than 65%.
[0030] In the following examples, unless otherwise specified, the cement used is PI 42.5 cement.
[0031] The aggregate gradations involved in the following examples are shown in Table 1.
[0032] Table 1 Aggregate gradation table
[0033] Example 1
[0034] This embodiment provides an ultra-high performance concrete, whose mix ratio is shown in Table 2, wherein the aggregate is low-silica iron tailings sand with a SiO2 content of 55%, and the gradation adopts the fine gradation in Table 1.
[0035] Table 2 Ultra-high performance concrete mix ratio (unit: kg / m 3 )
[0036] The ultra-high performance concrete provided in this embodiment is prepared in the following steps: (1) First, mix cement, aggregate, silica fume, fly ash and mineral powder and stir for 30 seconds to obtain a mixture; (2) mixing water, a water reducing agent, a defoaming agent and the mixture, and stirring for 150 seconds to obtain a fresh concrete slurry; (3) Finally, the fiber is mixed with the fresh concrete paste and stirred for 120 seconds to obtain a fresh ultra-high performance concrete paste, which is then cured and formed to obtain concrete, which is denoted as SMK.
[0037] Example 2
[0038] This embodiment provides an ultra-high performance concrete, which differs from Embodiment 1 only in that the ratio of aggregate to cementitious material is adjusted on the basis of Embodiment 1, specifically, the cementitious material is increased by 5%, the aggregate is correspondingly reduced by 5%, and the other components remain unchanged. The obtained concrete is recorded as USMK.
[0039] Example 3
[0040] This embodiment provides an ultra-high performance concrete, which is different from Embodiment 1 only in that the tailings sand involved in the tailings sand aggregate is selected from high-silica iron tailings with a SiO2 content of 75%, and the concrete is recorded as GWK1.
[0041] Example 4
[0042] This embodiment provides an ultra-high performance concrete, which is different from Embodiment 1 only in that the ratio of the cementitious material to the tailings sand aggregate is 1:0.5, and the concrete is recorded as CWK.
[0043] Example 5
[0044] This embodiment provides an ultra-high performance concrete, which is different from Embodiment 1 only in that the ratio of the cementitious material to the tailings sand aggregate is 1:2, and the concrete is recorded as ZWK.
[0045] Comparative Example 1
[0046] This comparative example provides an ultra-high performance concrete, which is different from Example 1 only in that the aggregate in the concrete is quartz sand aggregate, a coarse mix ratio is adopted, and the obtained concrete is used as a reference group, denoted as JZ.
[0047] Comparative Example 2
[0048] This comparative example provides an ultra-high performance concrete, which is different from Example 1 only in that the tailings sand aggregate adopts the coarse mix ratio in Table 1, and the obtained concrete is recorded as BWK.
[0049] Comparative Example 3
[0050] This comparative example provides an ultra-high performance concrete, which is different from Example 1 only in that the tailings sand aggregate adopts the medium proportion in Table 1, and the obtained concrete is recorded as MWK.
[0051] Comparative Example 4
[0052] This comparative example provides an ultra-high performance concrete, which is different from Example 1 only in that the ratio of the cementitious material to the tailings sand aggregate is 1:2.6, and the concrete is recorded as GWK2.
[0053] Test example
[0054] Test object: ultra-high performance concrete obtained from each embodiment and comparative example.
[0055] Test method: Test fluidity, compression and flexural strength according to GB50080 and GB50081.
[0056] Test results: The results are shown in Table 3.
[0057] Table 3 Performance of various ultra-high performance concretes
[0058] As shown in Table 3, JZ is an ultra-high performance concrete using quartz sand aggregate. Compared with JZ, the strength of BWK and MWK of coarse-graded and medium-graded tailings sand aggregates are significantly reduced at the three ages, and can no longer meet the requirement of ultra-high performance concrete with a compressive strength greater than 120 MPa. This is mainly because the strength of tailings sand is lower than that of quartz sand, which affects the overall strength.
[0059] Example 3 shows that the strength can be better improved by using high-silicon tailings.
[0060] Example 4 shows that the early strength of concrete can be increased by using a high mortar-sand ratio, but the increase in late strength is not obvious. Comparative Example 4 found that too low mortar-sand ratio will lead to a decrease in concrete strength, so the mortar-sand ratio should be selected within a suitable range.
[0061] Example 5 shows that the ultra-high performance concrete of the present invention, in which the amount of tailings sand aggregate added is very high, even when the mortar-sand ratio reaches 1:2, the 28-day compressive strength can still reach more than 120 MPa, meeting the requirement that the compressive strength of ultra-high performance concrete is greater than 120 MPa.
[0062] By changing the particle size distribution of tailings sand, the strength of SWK is lower than that of JZ in the early stage, but exceeds that of JZ in the later stage. This is mainly because the particle size distribution is updated after optimization, and the hydration products of concrete are not fully hydrated in the early stage, so the support effect of aggregate is more obvious. After the concrete is hydrated in the later stage, the micro-crack length of concrete with fine aggregate grading is smaller than the crack extension length, thus showing better mechanical properties.
[0063] The later mechanical properties of USWK are also better than those of JZ group. Considering that the hydration of cementitious materials leads to a decrease in the volume of hydration products, thus destroying the most densely packed particle grading, it is necessary to increase the components of cementitious materials in the batching to ensure the most densely packed after hydration and increase the mechanical properties.
[0064] The tailings sand aggregate provided by the present invention can be used to prepare concrete to enable ultra-high performance concrete to be densely packed, thereby improving the mechanical properties of the concrete, such as flexural strength and compressive strength.
[0065] The ultra-high performance concrete provided by the present invention can improve the flexural strength and compressive strength by adopting the above-mentioned cementitious material; the above-mentioned water-reducing agent can reduce the water-cement ratio; the defoaming agent can eliminate harmful bubbles of larger size, thereby improving the flexural and compressive strengths of the ultra-high performance concrete.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tailings sand aggregate, characterized in that: Including 40-90 mesh, 90-400 mesh, 400-1250 mesh tailings sand with a mass ratio of 1:0.6~3:0.4~2.
2. The tailings sand aggregate according to claim 1, characterized in that: Including 40-90 mesh, 90-400 mesh, 400-1250 mesh tailings sand with a mass ratio of 1:1~1.5:0.5~1.
3. The tailings sand aggregate according to claim 1, characterized in that: The tailings sand is selected from at least one of iron tailings, vanadium-titanium magnetite tailings, molybdenum tailings, copper tailings and gold tailings.
4. An ultra-high performance concrete, characterized in that: Contains 30-85wt% of the tailings sand aggregate described in any one of claims 1-3.
5. The ultra-high performance concrete according to claim 4, characterized in that: The content of the tailings sand aggregate is 35-70wt%.
6. The ultra-high performance concrete according to claim 4 or 5, characterized in that: It also includes a cementitious material, wherein the mass ratio of the cementitious material to the tailings sand aggregate is 1:0.5-2.5, preferably 1:0.5-2.0; Preferably, the cementitious material comprises cement and an auxiliary cementitious material; the auxiliary cementitious material is selected from at least one of fly ash, slag powder, silica fume, limestone powder and zeolite powder; and / or the particle size of the auxiliary cementitious material is 10-150 μm; More preferably, the cement is Portland cement.
7. The ultra-high performance concrete according to claim 6, characterized in that: The ultra-high performance concrete further comprises 1.5-2 wt % of an admixture; preferably, the admixture is selected from at least one of an expansive agent, a water reducing agent and a retarder.
8. The ultra-high performance concrete according to claim 7, characterized in that: It also includes 0.2-20wt% fiber; preferably, the aspect ratio of the fiber is 10-200, and more preferably, the fiber is selected from at least one of steel fiber, polyoxymethylene fiber, and polyvinyl alcohol fiber.
9. The ultra-high performance concrete according to claim 4, characterized in that: Calculated by weight, the components include: 400-1500 parts of cement, 600-1800 parts of tailings sand aggregate, 100-200 parts of silica fume, 0-200 parts of fly ash, 0-150 parts of mineral powder, 5-200 parts of fiber, 25-40 parts of water reducer, 0.01-0.2 parts of defoamer, and 150-190 parts of water; Preferably, the ultra-high performance concrete comprises the following components, measured by weight: 450-1000 parts of cement, 600-1600 parts of tailings sand aggregate, 120-180 parts of silica fume, 50-150 parts of fly ash, 50-100 parts of mineral powder, 100-150 parts of fiber, 30-40 parts of water reducer, 0.05-0.15 parts of defoamer, and 160-180 parts of water.
10. Use of the ultra-high performance concrete according to any one of claims 4 to 9 in building materials, pavement materials and bridge engineering.
Citation Information
Patent Citations
Corrosion-resistant iron tailing aggregate, corrosion-resistant concrete and preparation method thereof
CN110698098A
Cited By
Single-component waterproof mortar with low shrinkage rate and high compressive strength and preparation method thereof
CN120271289A
Single-component waterproof mortar with low shrinkage and high compressive strength and preparation method thereof
CN120271289B